Novel photoconductive Ag/nanostructure ruthenium oxide/p-type silicon Schottky barrier diode by sol-gel method - Al-Ghamdi, Ahmed A.; Al-Ghamdi, Attieh A.; Al-Hartomy, Omar A.; Nawar, Ahmed M.; El-Gazzar, E.; El-Tantawy, Farid; Yakuphanoğlu, Fahrettin (Springer, 2013)
A new Schottky photodiode of Ag/RuO2/p-Si/Al was successfully fabricated using spin-coating technique. The ruthenium oxide (RuO2) nanoparticles with an average size of 8 nm were synthesized using a sol-gel method. The crystal structure and morphology of the synthesized RuO2 were analyzed by means of X-ray diffraction, energy dispersive X-ray spectroscopy, transmission electron microscopy and selective area electron diffraction. The rectification ratio of the diode was found to be 112 at +/- 2 V. The ideality factor and barrier height values of the Ag/RuO2/p-Si/Al diode were obtained to be 1.47 and 0.55 eV, respectively. The Cheung-Cheung and Norde's models were used to determine the diode parameters. The photoresponse behavior of the fabricated Ag/RuO2/p-Si/Al diode was studied under various illumination intensities. The transient photocurrent results indicate that photocurrent under illumination is higher than the dark current and this indicates that the fabricated diode behaves as a photodiode. The capacitance-voltage-frequency measurements indicate that the capacitance of the diode depends on voltage and frequency. The obtained results suggest that the new Ag/RuO2/p-Si/Al diode can be used an optical switching device for optical sensor applications and are also expected to be generated in the future study.
Keywords: Ruthenium oxide nanoparticles; Schottky photodiode; Sol-gel